Nursing Intervention On Improving Quality Of Life Among Patients With Diabetic Renal Failure (The Review of Diabetic Studies, 2024)
Diabetic renal failure, a serious complication of diabetes mellitus, significantly impacts patients' quality of life (QoL), leading to physical, emotional, and social challenges. This narrative review aims to synthesize current literature on nursing interventions that effectively enhance QoL for patients with diabetic renal failure. The review identifies key strategies employed by nursing professionals, including comprehensive patient education, dietary management, psychological support, symptom management, and care coordination. Patient education emerges as a fundamental intervention, empowering individuals to manage their diabetes and renal health through informed decision-making regarding blood glucose monitoring and medication adherence. Dietary management is crucial, as nurses guide patients in making renal-friendly dietary choices that also accommodate diabetes control, thereby alleviating the physical burden of the disease. Psychological support is another essential component, addressing the emotional distress associated with chronic illness through regular mental health screenings and supportive counseling. Nurses are pivotal in recognizing signs of anxiety and depression, facilitating timely referrals to mental health professionals, and providing a therapeutic environment for patients to express their concerns. Effective symptom management, particularly for pain and fatigue, is vital for improving patients' daily functioning. Nurses can implement multimodal pain management strategies and assist in developing personalized activity schedules to help patients cope with fatigue. Moreover, the coordination of care among multidisciplinary teams enhances communication and ensures comprehensive management of patients' needs. By facilitating regular team meetings and effective discharge planning, nurses can promote seamless transitions in care, ultimately reducing hospital readmissions. In conclusion, a holistic approach to nursing interventions is imperative for improving the QoL of patients with diabetic renal failure. Continued research is necessary to refine these interventions and establish evidence-based practices that can further enhance patient outcomes. By prioritizing nursing care, healthcare systems can better support patients in managing their condition and achieving a higher quality of life.